Crustal structure at the western end of the North Anatolian Fault Zone from deep seismic sounding - B. Baier; H. Berckhemer; A. E. Karahan (Annals of Geophysics, 2001)
The first deep seismic sounding experiment in Northwestern Anatolia was carried out in October 1991 as part of the "German - Turkish Project on Earthquake Prediction Research" in the Mudurnu area of the North Anatolian Fault Zone. The experiment was a joint enterprise by the Institute of Meteorology and Geophysics of Frankfurt University, the Earthquake Research Institute (ERI) in Ankara, and the Turkish Oil Company (TPAO). Two orthogonal profiles, each 120 km in length with a crossing point near Akyazi, were covered in succession by 30 short period tape recording seismograph stations with 2 km station spacing. 12 shots, with charge sizes between 100 and 250 kg, were fired and 342 seismograms out of 360 were used for evaluation. By coincidence an M b = 4.5 earthquake located below Imroz Island was also recorded and provided additional information on Moho and the sub-Moho velocity. A ray tracing method orginally developed by Weber (1986) was used for travel time inversion. From a compilation of all data two generalized crustal models were derived, one with velocity gradients within the layers and one with constant layer velocities. The latter consists of a sediment cover of about 2 km with V p » 3.6 km/s, an upper crystalline crust down to 13 km with V p » 5.9 km/s, a middle crust down to 25 km depth with V p » 6.5 km/s, a lower crust down to 39 km Moho depth with V p » 7.0 km/s and V p » 8.05 km/s below the Moho. The structure of the individual profiles differs slightly. The thickest sediment cover is reached in the Izmit-Sapanca-trough and in the Akyazi basin. Of particular interest is a step of about 4 km in the lower crust near Lake Sapanca and probably an even larger one in the Moho (derived from the Imroz earthquake data). After the catastrophic earthquake of Izmit on 17 August 1999 this significant heterogeneity in crustal structure appears in a new light with regard to the possible cause of the Izmit earthquake. Heterogeneities in structure are frequently also heterogeneities in strength and stress that impede or even lock rupture. The Izmit earthquake is discussed in relation to a large stepover or jog at the North Anatolian Fault.